Adaptasi Komunikasi Antar Budaya Mahasiswa Rantau Itera dalam Menghadapi Gegar Budaya di Lampung - Nadila Putri Effendi; Purwanto; Anna Gustina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The inter-regional mobility of students, particularly towards higher education institutions such as the Institut Teknologi Sumatera (ITERA), presents significant socio-cultural adaptation challenges. This research aims to analyze the intercultural communication adaptation of ITERA's out-of-region students in navigating culture shock in Lampung. Students from diverse regions across Indonesia face substantial challenges in adjusting to a novel socio-cultural environment. Employing a qualitative research design with a case study approach, this study involved in-depth interviews with out-of-region students and participatory observation. The findings reveal that these students undergo various stages of culture shock, ranging from denial to integration. This adaptation process is significantly influenced by intercultural communication competence, which encompasses understanding and respecting differences in values, norms, and symbols. Internal factors, such as individual motivation and ability, as well as external factors, including environmental support and interaction with the local community, play a crucial role in facilitating adaptation. This research also identifies effective adaptation strategies, such as building social networks, acquiring local language skills, and participating in cultural activities. The implications of this study underscore the importance of developing orientation and support programs for out-of-region students, and promoting awareness of the significance of intercultural communication within the academic environment.